Identifying of the fuel-air mixing, mixture formation, ignition and combustion characteristic in the combustion chamber - Zainal, Rabi’atulawwaliah; Saiful Azam, Syafiqah Ruqaiyah; Khalid, Amir; Jaat, Norrizam; Amirnordin, Shahrin Hisham (Penerbit UTHM, 2020)
The area within the cylinder where the fuel/air mix is ignited is known as combustion chamber. As the piston compresses the fuel/air mixture and makes contact with the spark plug, the mixture is combusted in the form of energy and pushed out of the combustion chamber. The purpose of this technical paper is basically discussing about the combustion chamber which is more specific to injection fuel. This paper represents the identifying of the fuel-air mixing, mixture formation, ignition and combustion characteristic in the combustion chamber. The methodology used were by choosing the best article with the outcome related to this study and related to this research parameter. There are included the ignition system which are ignition system in combustion system (plasma) and ignition system in combustion system (laser) plasma is a new compact generator of high-voltage nanosecond pulses on the basis of the drift step recovery diodes combined with a control unit. Laser ignition is considered to be one of the most promising future ignition concepts for internal combustion engines. It not only combines requirement of reduction of pollutant emissions but also improves engine efficiencies.